2014
DOI: 10.1080/10410236.2013.841531
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Cigarette Warning Labels: Examining the Impact of Graphics, Message Framing, and Temporal Framing

Abstract: This study examines the effectiveness of cigarette warning labels, with a specific focus on the impact of graphics, message framing (gain vs. loss), and temporal framing (present-oriented vs. future-oriented) among nonsmokers in the United States. A controlled experiment (N = 253) revealed that graphic warning labels were perceived as more effective, stronger in argument strength, and were generally liked more compared to text-only labels. In addition, loss-framed labels, compared to their gain-framed counterp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
66
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 31 publications
1
66
1
Order By: Relevance
“…This follows from the sign effect (Thaler, 1981); that is, the subjective value of gains declines quite rapidly over time, whereas for losses this is much less the case, minimizing the advantage of gains over losses for long-term health outcomes. Other more recent studies (De Bruijn & Budding, 2016;De Bruijn, Spaans, Jansen, & van't Riet, 2016) have found interactions between message framing and temporal context that counter the findings by Gerend and Cullen (2008), and still others have been unable to find significant interactions between message framing and temporal context (Bernstein, Wood, & Erickson, 2016;Nan, Zhao, Yang, & Iles, 2014).…”
Section: Gain-loss Asymmetry In Temporal Discountingmentioning
confidence: 46%
“…This follows from the sign effect (Thaler, 1981); that is, the subjective value of gains declines quite rapidly over time, whereas for losses this is much less the case, minimizing the advantage of gains over losses for long-term health outcomes. Other more recent studies (De Bruijn & Budding, 2016;De Bruijn, Spaans, Jansen, & van't Riet, 2016) have found interactions between message framing and temporal context that counter the findings by Gerend and Cullen (2008), and still others have been unable to find significant interactions between message framing and temporal context (Bernstein, Wood, & Erickson, 2016;Nan, Zhao, Yang, & Iles, 2014).…”
Section: Gain-loss Asymmetry In Temporal Discountingmentioning
confidence: 46%
“…Similar effects were obtained for recycling intentions in adults (White, MacDonnell, & Dahl, 2011) and fruit intake intentions in undergraduate students (Hing Lo et al, 2012). In contrast, other research either has failed to detect an interaction between message frame and temporal context (Bernstein et al, 2016;Nan et al, 2015) or has found opposite results (Gerend & Cullen, 2008). For instance, in a study on alcohol consumption in undergraduate students, Gerend and Cullen (2008) found that short-term consequences were only persuasive when combined with gain-framed messages.…”
Section: Message Framing and Temporal Contextmentioning
confidence: 48%
“…Nevertheless, outcomes in message framing typically compare positive with negative consequences rather than short-term consequences with long-term consequences. To our knowledge, only a handful of studies have investigated how temporal context influences intentions (Bernstein, Wood, & Erickson, 2016;Dimmock, Jackson, Clear, & Law, 2013;Gerend & Cullen, 2008;Nan, Zhao, Yang, & Iles, 2015;Orbell & Kyriakaki, 2008) and, to a lesser extent, how temporal context interacts with message frame to influence intentions (Bernstein et al, 2016;De Bruijn, Spaans, Jansen, & Van 't Riet, 2016;Gerend & Cullen, 2008;Nan et al, 2015;Orbell & Kyriakaki, 2008). Only one study has investigated how temporal context interacts with message frame to influence behavioral expectations (Hing Lo et al, 2012), and no study has focused on resolve outcomes.…”
Section: Message Framing and Temporal Contextmentioning
confidence: 99%
See 2 more Smart Citations